Living language : an introduction to linguistic anthropology - Ahearn, Laura M., 1962- (Blackwell primers in anthropology ;, 2012)
"Accessible and clearly written, Living Language: An Introduction to Linguistic Anthropology introduces readers to the study of language in real-life social contexts around the world through the contemporary theory and practice of linguistic anthropology. A highly accessible introduction to the study of language in real-life social contexts around the world Combines classic studies on language and cutting-edge contemporary scholarship and assumes no prior knowledge in linguistics or anthropology Provides a unifying synthesis of current research and considers future directions for the field Covers key topics such as: language and gender, race, and ethnicity; language acquisition and socialization in children and adults; language death and revitalization; performance; language and thought; literacy practices; and multilingualism and globalization"--